PENGARUH DAUN ASAM JAWA (Tamarindus Indica Linn) TERHADAP PERTUMBUHAN CANDIDA ALBICANS - Fakhrurrazi Fakhrurrazi; Rachmi Fanani Hakim; Cut Nyak Keumala (Journal of Syiah Kuala Dentistry Society, 2016)
Oral candidiasis is a fungi infection disease in oral cavity caused by overgrowth of Candida albicans. Tamarind leaf (Tamarindus indica Linn) is herbal plant contains flavonoid, saponin, tanin, alkaloid, and triterpenoid that could be use as alternatif medicine for candidiasis theraphy. This study aimed to assay effect of tamarind leaf on Candida albicans growth. Tamarind leaf was extracted using soxhletasion methode. Antifungal activity of tamarind leaf on growth of Candida albicans was assay by counting colony in different consentration of tamarind leaf using Concentration (10%-100%). Statistic result of ANAVA using data showed that tamarind leaf had effect on Candida albicans growth.Keywords: Candidiasis, Candida albicans, Tamarind leaf